TECHNO ECONOMIC FEASIBILITY OF GEOTHERMAL POWER PLANT IN INDONESIA USING RETSCREEN CONSIDERING CARBON CREDIT MECHANISM TO ACHIEVE INDONESIAâS NDC 2060 - Chrisantia Husein, Maura
Indonesia’s geothermal reserves made the country has abundant geothermal energy potential but its utilization is still minimum due to insufficient investor participation. In the PLN Power Supply Generation (RUPTL PLN) indicates that there are a potential of 330 MW geothermal power plant in Gunung Kembar. This study conducts a feasibility analysis of Gunung Kembar 330 MW geothermal power plant with the aim of attracting investors to engage in renewable energy utilization project and achieve the National Determined Contributions (NDC) for the year 2060. Four Scenarios were developed to determine the feasibility of the project based on the carbon credit prices and the lifetime of the project. First scenario was developed to assess the current condition of Indonesia’s profitability on geothermal power plant considering a 2 USD per ton CO2 as stated by UU. No 7 2021 and a lifetime of 25 years. Second scenario considered the increase of incentives from 2 USD per ton CO2 to 18 USD per ton CO2 with the same lifetime as the first scenario. Third scenario considered the change in the lifetime project from 25 years to 30 refers to existing Sarulla 330 MW geothermal power plant. And the last scenario is the proposed scenario with the carbon credit price is fixed to 50 ton per CO2 refers to the suggestions of the International Monetary Fund, and the lifetime of the project are fixed to 30 years. RETScreen modelling results showed that the suitable power capacity for 1 unit from 330 MW is to be 21 MW based on the consideration of the availability of steam flow and other aspects. Financial analysis showed that the Internal Rate of Return from Scenario I is 11.6% which is slightly above the discount rate (10%), the Scenario II IRR and NPV are higher than the Scenario I but still high on LCOE for 0,091. Scenario III and Scenario IV are also have a positive IRR and NPV with lower LCOE than the Scenario I and II and showed that the project is very profitable for Indonesia’s investors. Therefore, it is recommended for Indonesia’s government to increase the carbon pricing in the nation for 50 USD per ton CO2 in order to gain more profit and attract investors to engage in investing on the renewable energy project.